2021
DOI: 10.3390/ijerph182312726
|View full text |Cite
|
Sign up to set email alerts
|

Group Medical Care: A Systematic Review of Health Service Performance

Abstract: Group care models, in which patients with similar health conditions receive medical services in a shared appointment, have increasingly been adopted in a variety of health care settings. Applying the Triple Aim framework, we examined the potential of group medical care to optimize health system performance through improved patient experience, better health outcomes, and the reduced cost of health care. A systematic review of English language articles was conducted using the Cochrane Controlled Trials Register … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
(129 reference statements)
0
7
0
Order By: Relevance
“…A systematic review of patient-centered experience in GMVs/shared medical appointments for a wide range of conditions found many benefits to GMVs over individual care, including extended time, higher levels of patient satisfaction overall and with patient-clinician relationships, benefits of peer support, and high levels of engagement among patient participants [ 73 ]. Recently, a systematic review evaluating the potential of GMVs to address the Triple Aim of healthcare improvement found evidence of benefits of GMVs in all three aims [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of patient-centered experience in GMVs/shared medical appointments for a wide range of conditions found many benefits to GMVs over individual care, including extended time, higher levels of patient satisfaction overall and with patient-clinician relationships, benefits of peer support, and high levels of engagement among patient participants [ 73 ]. Recently, a systematic review evaluating the potential of GMVs to address the Triple Aim of healthcare improvement found evidence of benefits of GMVs in all three aims [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence indicates group visits may have a positive impact on health service delivery. In studies to date, group visits have been shown to (a) be more cost-effective than one-on-one consultations [5,6], (b) increase accessibility to healthcare in diverse and/or underserved populations [7], (c) be well-received by patients and providers [5,8], and (d) be effective in managing conditions such as diabetes [9,10] and chronic pain [11,12]. The group dynamic can provide additional benefits to patients where a sense of human connection and empowerment may be fostered alongside increased capacity for patient education [3,13].…”
Section: Introductionmentioning
confidence: 99%
“…The group dynamic can provide additional benefits to patients where a sense of human connection and empowerment may be fostered alongside increased capacity for patient education [3,13]. To date, no adverse effects have been associated with group-delivered health care [6]. Although several studies suggest patients attending group visits may receive more comprehensive care (than those attending one-on-one care), there may be disadvantages to the model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To increase access to MWV among our older adult primarily Black patients in Detroit, thereby increasing our ability to address health maintenance gaps (HMG), our team adapted these visits to a shared medical appointment group visit format ( Noffsinger, 1999 ). Group visits have been shown to lead to positive health outcomes through improved patient experience ( Cunningham et al, 2021 ), specifically in patients with chronic pain ( Lestoquoy et al, 2017 ), attempting weight loss ( Axten et al, 2017 ) as well as for patients who are older ( Cherniack, 2014 ) and needing advanced care planning ( Lum et al, 2016 , Lum et al, 2017 ). Group visits effectiveness could be due to increased patient satisfaction ( Egger et al, 2015 , Heyworth et al, 2014 ) and easing primary care provider burden ( Egger et al, 2015 , Stults et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%